School Library Staffing Ratios and Student Outcomes: Challenging the Conventional Wisdom - EveryLibrary Institute Staff (The Political Librarian, 2023)
This report is an analysis of the current data available on the impact of school libraries and librarians and media specialists within their school communities. It includes a broad diagnosis and establishes general goals for all advocates to be effective.